Integration of RNA-seq and ATAC-seq analyzes the effect of low dose neutron-γ radiation on gene expression of lymphocytes from oilfield logging workers - Li, Weiguo; Gao, Gang; Pan, Yan; Wang, Ziqiang; Ruan, Jianlei; Fan, Li; Shen, Yingjie; Wang, Haiqing; Li, Mian; Zhang, Pinhua; Fang, Lianying; Fu, Jinghong; et al. (Frontiers in Chemistry, 2023)
Objective: Although radiation workers are exposed to much lower doses of neutron-γ rays than those suffered in nuclear explosions and accidents, it does not mean that their health is not affected by radiation. Lower doses of radiation do not always cause morphological aberrations in chromosomes, so more sophisticated tests must be sought to specific alterations in the exposed cells. Our goal was to characterize the specific gene expression in lymphocytes from logging workers who were continuously exposed to low doses of neutron-γ radiation. We hypothesized that the combination of cell type-specific transcriptomes and open chromatin profiles would identify lymphocyte-specific gene alterations induced by long-term radiation with low-dose neutron-γ-rays and discover new regulatory pathways and transcriptional regulatory elements. Methods: Lymphocytes were extracted from workers who have been occupationally exposed to neutron-γ and workers unexposed to radiation in the same company. mRNA-seq and ATAC-seq (Assay for Transposase-Accessible Chromatin with high-throughput sequencing) were performed, followed integrative analysis to identify specific gene regulatory regions induced by neutron-γ radiation. A qPCR assay was then performed to verify the downregulation of RNA coding for ribosomal proteins and flow cytometry was used to detect ribosomal protein expression and cell cycle alterations. Results: We identified transcripts that were specifically induced by neutron-γ radiation and discovered differential open chromatin regions that correlated with these gene activation patterns. Notably, we observed a downward trend in the expression of both differentially expressed genes and open chromatin peaks. Our most significant finding was that the differential peak upregulated in ATAC-seq, while the differential gene was downregulated in the ribosome pathway. We confirmed that neutron-γ radiation leads to transcriptional inhibition by analyzing the most enriched promoters, examining RPS18 and RPS27A expression by qPCR, and analyzing protein-protein interactions of the differential genes. Ribosomal protein expression and cell cycle were also affected by neutron-γ as detected by flow cytometry. Conclusion: We have comprehensively analyzed the genetic landscape of human lymphocytes based on chromatin accessibility and transcript levels, enabling the identification of novel neutron-γ induced signature genes not previously known. By comparing fine-mapping of open chromatin and RNA reads, we have determined that neutron-γ specifically leads to downregulation of genes in the ribosome pathway, with pseudogenes potentially playing a crucial role.